The Politics of Culture and the Art of Dissent in Early Modern Japan - Farge, William J. (Social justice, 2006)
Part of a special issue on art, power, and social change. In the late 17th century and the early 18th century, Japan underwent a period of decline. After 1716, the administration of Tokugawa Tsunayoshi introduced emergency economic measures intended to reduce the disparity between the increasing power and influence of the merchant class and the social and economic decline of the samurai, but conditions continued to deteriorate. In such environments of social instability, people wish to make their views known in a compelling and cautious manner, and satire emerges as an expression of dissatisfaction. One of the prominent satirists in early modern Japan was Baba Bunk̄o, and it is not hyperbole to suggest that his writings and lectures, which ended with his arrest and execution in 1759, set the stage for the Meiji Restoration that occurred 100 years later. The writer discusses Bunk̄o's work in detail.